An 871 Response Survey Dataset on Public Perceptions of Education for Sustainable Development, Digital Competencies, and Industry 4.0 - Ioannis Ch. Lampropoulos; Olga Astara (Sustainability Research in the Mediterranean, 2026)
The progressive integration of digital technologies into education, together with the rising policy salience of sustainable development, has intensified the demand for datasets capable of sustaining interdisciplinary educational research. This paper presents a structured survey dataset documenting public perceptions of the relationships among Education for Sustainable Development (ESD), digital competencies, and the Fourth Industrial Revolution (Industry 4.0). Data were collected through an online questionnaire administered over seven consecutive days, yielding 871 valid responses and a curated dataset of 34 variables. These variables cover demographic characteristics, educational background, digital competencies, sustainability awareness, and perceptions of technology supported learning and sustainable development. The dataset combines categorical, binary, ordinal, and Likert scale measures, accommodating descriptive, correlational, multivariate, and predictive analyses. Its interdisciplinary scope and standardized coding make it a reusable resource for researchers, educators, and policymakers concerned with digital transformation, sustainability education, and educational innovation. The dataset further supports secondary analysis, cross national comparison, and the empirical validation of theoretical models linking ESD to Industry 4.0.